Delayed positivity of serological reactions in secondary syphilis against the background of severe HIV-induced immunosuppression - Sergey V. Prozherin; Anzhelika S. Podymova (State Scientific Center of Dermatovenereology and Cosmetology, 2023)
In recent decades, there has been an increase in syphilis associated with HIV infection cases, especially among men who have sex with men. The global prevalence of syphilitic infection among people living with HIV exceeds population rates. Concomitant HIV infection can affect not just the clinical course of syphilis, but also the production of antibodies to Treponema pallidum. In the presence of severe immunodeficiency in patients with HIV infection associated with secondary syphilis, the results of non-treponemal and/or treponemal tests may be false-negative or may become positive at a later date. Such cases are known, they occur infrequently and cause some diagnostic difficulties. The article presents a clinical observation of delayed positivity of serological reactions in secondary syphilis in a 23-year-old HIV-positive man from the authors' practice. The tactic of managing HIV-infected patients with clinical symptoms of the secondary period syphilis and negative results of serological tests is discussed.